2008
DOI: 10.1128/iai.01530-07
|View full text |Cite
|
Sign up to set email alerts
|

IsdA ProtectsStaphylococcus aureusagainst the Bactericidal Protease Activity of Apolactoferrin

Abstract: An important facet of the Staphylococcus aureus host-pathogen interaction is the ability of the invading bacterium to evade host innate defenses, particularly the cocktail of host antimicrobial peptides. In this work, we showed that IsdA, a surface protein of S. aureus which is required for nasal colonization, binds to lactoferrin, the most abundant antistaphylococcal polypeptide in human nasal secretions. The presence of IsdA on the surface of S. aureus confers resistance to killing by lactoferrin. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 72 publications
(96 reference statements)
1
50
0
Order By: Relevance
“…Such binding likely makes a contribution to human nasal carriage, allowing the bacterium to adhere to its host. Conversely, the C-terminal domain of IsdA is required for survival on live human skin via its ability to alter cellular biophysical properties, resulting in more hydrophilic cells with increased resistance to skin fatty acids (11). A question remains as to why an adhesin able to bind loricrin might also be involved in fatty acid resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such binding likely makes a contribution to human nasal carriage, allowing the bacterium to adhere to its host. Conversely, the C-terminal domain of IsdA is required for survival on live human skin via its ability to alter cellular biophysical properties, resulting in more hydrophilic cells with increased resistance to skin fatty acids (11). A question remains as to why an adhesin able to bind loricrin might also be involved in fatty acid resistance.…”
Section: Resultsmentioning
confidence: 99%
“…3) suggested that cytokeratin K10, loricrin, and involucrin all bind to the same IsdA region. Previous studies have shown that many protein ligands bind to the N-terminal NEAT domain of IsdA (7,11), whereas the Cterminal domain is involved in resistance to human skin fatty acids and antimicrobial peptides (10). Using the whole-cell adhesion assay, the NEAT domain was found to be responsible for the IsdA-mediated binding of S. aureus to loricrin, involucrin, and cytokeratin K10, as a mutant lacking the NEAT domain (SRC008) demonstrated reduced binding, whereas SRC009 (isdA⌬C) did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These resistance genes include dlt-operon, which is responsible for D-alanylation of teichoic acid; mprF, which mediates the incorporation of lysyl-phosphatidylglycerol in the cytoplasmic membrane (both of these genes decrease the negative net charge of the cell envelope); and the vraFG genes of a transport system [46,47,[49][50][51]. Other reported resistance mechanisms include protease inhibitors, such S. aureus IsdA surface protein [52], and biofilm stabilizers such exopolysaccharide intercellular adhesin (PIA) [53]. Nevertheless, bacterial resistance mechanisms to AMPs differ with regard to efficiency, specificity and distribution among species [46], and natural AMPs have evolved to avoid some of these resistance mechanisms.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Briefly, the Isd system in S. aureus consists of nine iron-regulated proteins: IsdA, IsdB, IsdC, and IsdH/HarA, which are cell wall-anchored surface proteins, and IsdDEF, which constitute a membrane-localized transporter, and, finally, IsdG and IsdI, which encode heme-degrading enzymes in the cytoplasm (12). IsdA is highly expressed on the cell wall of iron-limited S. aureus and, in addition to several other reported functions (13)(14)(15), is effective at scavenging heme (16,17). Additional reported functions of Isd proteins include the binding by IsdB of hemoglobin (18), IsdH/ HarA-dependent binding of haptoglobin and haptoglobin-hemoglobin (19), and heme binding by IsdC and IsdE (20 -23).…”
mentioning
confidence: 99%